Performance parameters of a unity power factor rectifier-inverter structure - Zeeshan Iqbal Siddiqui (2008)
The objective of this work is to investigate the performance parameters of a recently proposed rectifier inverter structure which makes use of bi-directional switches to improve power factor and reduce harmonics. The rectifier inverter has been subjected to supply voltage unbalances, and its behavior under these non ideal operating conditions has been observed.